Design, Synthesis, and Biological Evaluation of Dual c-Met/HDAC Inhibitors Bearing 2-Aminopyrimidine Scaffold - Zhang, Qingwei; Xu, Guili; Bao, Ya; Jiao, Minru; Li, Jianqi (Pharmaceutical Fronts, 2020)
A series of c-Met/histone deacetylase (HDAC) bifunctional inhibitors was designed and synthesized by merging pharmacophores of c-Met and HDAC inhibitors. Among them, the most potent compound, 2o, inhibited c-Met kinase and HDACs, with IC50 values of 9.0 and 31.6 nM, respectively, and showed efficient antiproliferative activities against both A549 and HCT-116 cancer cell lines with greater potency than an equimolar mixture of the respective inhibitors of the two enzymes: crizotinib and vorinostat (SAHA). Our study provided an efficient strategy for the discovery of multitargeted antitumor drugs.
Keywords: c-Met/HDAC inhibitor; dual inhibitor; hybrid; antitumor drugs; multipharmacology